Primary structure of human neutrophil elastase. - Sinha, S (1987)
The complete amino acid sequence of human neutrophil elastase has been determined. The protein consists of 218 amino acid residues, contains two asparagine-linked carbohydrate side chains, and is joined together by four disulfide bonds. Comparison of the sequence to other serine proteinases indicates only moderate homology with porcine pancreatic elastase (43.0%) or neutrophil cathepsin G (37.2%). In particular, many of the residues suggested to play important roles in the mechanism by which the pancreatic elastase functions are significantly changed in the neutrophil enzyme, indicating alternative types of binding with the human proteinase.